Inventarisasi Selaginellaceae di Hutan Lindung Aek Nauli Parapat Sumatera Utara - Jamilah Nasution; Ida Fauziah; Ferdinand Susilo (Biogenesis: Jurnal Ilmiah Biologi, 2017)
This research aims to determine the types of Selaginella in the field and to know the existence of species within a community. This study was conducted by collecting specimens from the field followed by inventory and identification of Selaginella species, as well as recording environmental conditions.The results of this study obtained 5 types of Selaginella: Selaginella intermedia, Selaginella kityyae, Selaginella longariastata, Selaginella ornata and Selaginella willdenovii. Based on their habitat Selaginella intermedia, Selaginella kityyae, Selaginella longariastata and Selaginella willdenovii found in field, have a terrestrial habitus spread, whereas Selaginella ornata is an upright epilithic terrestrial, with each species found mostly in clusters and dominate in an area.